Knowledge and practice of early essential newborn care among health professionals in Indonesia - Agus, Yenita; Elany, Dinda Assyifa Putri; Lestari, Kustati Budi (Universitas Aisyiyah Yogyakarta, 2025)
Indonesia's neonatal mortality rate stands at 12 deaths per 1,000 live births, driven by prematurity, asphyxia, and congenital anomalies. Inconsistent Essential Newborn Care (EENC) implementation fuels preventable first-24-hour deaths. This study aims to assess EENC knowledge and practices among Indonesian health professionals. A cross-sectional survey of 132 experienced providers (>3 years in delivery/perinatology) from hospitals, community health centers, and independent midwifery practices used a validated questionnaire via Google Forms. Descriptive statistics and chi-square tests identified associations (P<0.05). Overall, 66.4% showed poor EENC knowledge. Strengths included breastfeeding cues (99.2% correct attachment; 93.9% rooting), but deficits marked contraindications (34.8% for maternal hemorrhage >1,000 ml; 49.2% post-birth wheezing). Practices excelled in basics (93.2% recognized hypothermia/cord/skin-to-skin/breastfeeding/infection prevention; 90.2% upright positioning) yet faltered in sequencing: only 15.9% prioritized birth time announcement then thorough drying, 50.8% suctioned airways immediately, and 48.5% endorsed supine second-stage positioning. Workplace significantly affected knowledge (χ²=9.467, P=0.009): hospitals were the worst (79.1% poor), and independent midwifery practices were the best (33.3%). Age, education, experience, and training showed no association. Procedural sequencing and contraindication gaps stem from heavy workloads and patchy training. Skills-focused programs with supervision and supportive settings are essential to boost competency and decrease deaths. Observational studies should capture real behaviors and assess training/policy impacts on newborn outcomes.